EFFECTIVENESS OF THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF STAD TYPE WITH SAVI-CTL APPROACH IN MATHEMATICS LEARNING TO CLASS VII STUDENTS AT SMPN 2 BONTONOMPO SELATAN IN GOWA DISTRICT - Kiki Rezky Amalia (Universitas Negeri Makassar, 2018)
The study aims at describing the effectiveness of cooperative learning model of STAD type with SAVI-CTL approach in Mathematics learning to Class VII students at SMPN 2 Bontonompo Selatan in Gowa District. The study is pre-experiment research. The populations were all class VII students at SMPN 2 Bontonompo Selatan in Gowa District. The sample was class VII.C as the experiment class chosen by employing simple random sampling technique. Data collections were students’ learning result, students’ activities during the learning process, and students’ responses on the implementation of learning model. Data were analyzed by using descriptive analysis and inferensial analysis. The results of the study reveal that the students’ learning result in Mathematics is in high category with the mean 81.17 and deviation standard 6.64, the classical completeness level is 88%, the mean of normalized gain of learning result is in high category, students’ activities in learning are in Tended to be Active category with the mean 3.28, and students’ responses on the implementation of cooperative model of STAD type with SAVI-CTL approach is in positive category with the mean 3.55. In general, the conclusion is the cooperative model of STAD type with SAVI-CTL approach is effective to be applied in Mathematics learning to Class VII Students at SMPN 2 Bontonompo Selatan in Gowa District.